Brugada syndrome diagnosed in a young woman occurring postpartum: case report and literature review - Li, Wenhui; Pan, Xiaoyu; Cheng, Jiaoying (Frontiers in Cardiovascular Medicine, 2025)
Brugada syndrome (BrS), a hereditary cardiac channelopathy linked to malignant arrhythmias and sudden cardiac death, exhibits significant gender disparity with higher prevalence in males. This case report details a rare occurrence of BrS in a 32-year-old primigravida who suffered an acute cardiopulmonary arrest 2 h postpartum. The patient, with no prior cardiac history or family history of sudden death, underwent an uncomplicated delivery but developed sudden pulselessness post-transfer to the ward. Immediate resuscitation and subsequent evaluations revealed a type I Brugada ECG pattern, while structural cardiac abnormalities, electrolyte imbalances, and other etiologies were excluded. Although genetic testing was negative for pathogenic variants, the clinical diagnosis of BrS was made. An implantable cardioverter-defibrillator (ICD) was implanted for secondary prevention. This case underscores the importance of recognizing BrS in atypical populations, advocating for heightened vigilance in postpartum women with unexplained cardiac events. Further research into female-specific risk factors and collaborative care frameworks is essential to optimize maternal and neonatal outcomes.